2022 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) 2022
DOI: 10.1109/vl/hcc53370.2022.9833107
|View full text |Cite
|
Sign up to set email alerts
|

Is Assertion Roulette still a test smell? An experiment from the perspective of testing education

Abstract: Test smells are commonly perceived as having a negative impact on software maintainability and correctness. Research has shown that Assertion Roulette is the most pervasive smell in industrial and open-source systems. However, some recent studies argue that the impact of Assertion Roulette is not as severe as previously believed, and developers usually consider it acceptable.The controversy over the impact of Assertion Roulette also exists in the area of testing education. To assess the impact of Assertion Rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Therefore, the investigation of the multiple asserts seems to increase the debugging time, and therefore, the Assertion Roulette is negatively impacting the students' debugging process. Our observation brings an alternate perspective with respect to the recent findings of Bai et al [7], who conjectures that Assertion Roulette may no longer be considered a code smell. In fact, Bai et al [7] demonstrated, through a controlled classroom experiment, that Assertion Roulette does impact neither the frequency of testing nor the accuracy of the test cases.…”
Section: Rqsupporting
confidence: 48%
See 4 more Smart Citations
“…Therefore, the investigation of the multiple asserts seems to increase the debugging time, and therefore, the Assertion Roulette is negatively impacting the students' debugging process. Our observation brings an alternate perspective with respect to the recent findings of Bai et al [7], who conjectures that Assertion Roulette may no longer be considered a code smell. In fact, Bai et al [7] demonstrated, through a controlled classroom experiment, that Assertion Roulette does impact neither the frequency of testing nor the accuracy of the test cases.…”
Section: Rqsupporting
confidence: 48%
“…Our observation brings an alternate perspective with respect to the recent findings of Bai et al [7], who conjectures that Assertion Roulette may no longer be considered a code smell. In fact, Bai et al [7] demonstrated, through a controlled classroom experiment, that Assertion Roulette does impact neither the frequency of testing nor the accuracy of the test cases. We argue that Assertion Roulette is a program comprehension problem.…”
Section: Rqsupporting
confidence: 48%
See 3 more Smart Citations